Myanmar Politics, Economy and Society (Second Edition) - Simpson, Adam; Farrelly, Nicholas (Taylor & Francis, 2024)
This new edition of Myanmar: Politics, Economy and Society provides a sophisticated yet accessible overview of the key political, economic and social challenges facing contemporary Myanmar and explains the complex historical and ethnic dynamics that have shaped the country. Thoroughly revised, the book analyses the context and tragic consequences of the military coup in February 2021 and the COVID-19 pandemic. With clear and incisive contributions from the world's leading Myanmar scholars, this book assesses the policies and political reforms that have provoked contestation in Myanmar's recent history and driven both economic and social change. In this context, questions of economic ownership and control and the distribution of natural resources are shown to be deeply informed by long-standing fractures among ethnic and civil-military relations. The chapters analyse the key issues that constrain or expedite societal development in Myanmar and place recent events of national and international significance in the context of its complex history and social relations. The book provides detailed analysis of the coup, which overturned a decade of political and economic reforms and threw the country into chaos. It explains the drivers for the coup, how it has impacted on the country and the future prospects for accountability and justice. Filling a gap in the market, this research textbook and primer will be of interest to upper undergraduates, postgraduates and scholars of Southeast Asian politics, economics and society and to journalists and professionals working within governments, companies and other organisations.